A new proposal of a simple model for the lateral-torsional buckling of unrestrained steel I-beams in case of fire: Experimental and numerical validation - Vila Real, P.M.M. (2010)
The behaviour of Steel I-Beams exhibiting lateral-torsional buckling at elevated temperature has been studied by means of experimental and numerical analysis. The authors in an earlier paper have presented an analytical formula for the buckling resistance moment in the fire design situation. This new proposal, different from the actual proposal of the Eurocode 3 Part 1.2 has been validated in this work by comparison with the results from a set of 120 experimental and numerical tests performed on IPE 100 beams, submitted to temperatures varying from room temperature to 600 °C. The numerical simulations have been based on the measured geometrical dimensions of the cross-sections, the longitudinal imperfections, i. e. the out of straightness of the beams, the residual stresses and the yield strength. The Eurocode simple model promotes ultimate loads that depend mainly on the non-dimensional slenderness of the beams. The analytical results provided by the Eurocode 3, for a certain range of the slenderness, appear to be unsafe when compared with the numerical and experimental results. It is shown that the new proposal is safer than the Eurocode 3 formulas.